Corporate Environmental Liability in Albania: Integrating Legal Frameworks with Educational Compliance Practices - Filip, Elena; Liçenji, Anjeza; Katro, Kestrin (European Journal of Social Science Education and Research, 2025)
As global awareness of environmental degradation grows, corporations are increasingly expected to take responsibility for reducing their environmental impact. In Albania, businesses are recognized as significant contributors to ecological harm, with the legal framework, including the Civil Code, Criminal Code, and Law on Environmental Protection, assigning them environmental responsibility alongside natural persons. A key mechanism to address this responsibility is education: training employees and managers on compliance practices ensures effective implementation and fosters a green culture within organizations. Although compliance programs are not explicitly codified in Albanian law, they remain closely linked to good governance, helping companies prevent environmental damage, avoid fines, and strengthen operational accountability. By integrating education, training, and environmental compliance into their corporate strategies, Albanian companies can enhance stakeholder engagement, improve their market reputation, and achieve sustainable development over time, aligning with national and international environmental standards. This way, we aim to highlight that environmental education, beyond reinforcing compliance, is increasingly a strategic driver for promoting environmental awareness and sustainability in corporate operations, ultimately supporting long-term development and corporate success.